A bill to incorporate the Milton Savings Bank ... the town of Militon (House doc. (North Carolina. General Assembly. House of Commons), 1848)
1848 North Carolina House of Commons Bill to incorporate the Milton Savings Bank in Milton, County of Caswell. The bill included an issuance of stock, the powers and duties of the board of directors, as well as other relevant corporate matters.